Women Crossing Borders: A comme-il-faux Exercise - Dagan, Uri; Smoler, Marayan (Israel, 2004)
Duration: 00:03:00 A group of students from the Visual Communications Department of the Bezalel Academy of Arts, Jerusalem, organize a fashion parade within the premises of the security wall. Uris Dagan goal was to make a cynical statement on the wall, without being over-dramatic, to capture the contrast between the clothes, the wall and the fashion smile, especially as comme-il-faux is a very exclusive and expensive shop. Uris Dagan Uri was sent to prison for refusing to serve in the territories and spent 24 days among walls.